KARAKTERISTIK BAYI PENDERITA GASTROENTERITIS YANG DIRAWAT INAP DI RSUD PURI HUSADA TEMBILAHAN TAHUN 2011-2012 - Rivando Fernandus; Sori Muda Sarumpaet; Hiswani Hiswani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Gastroenteritis disease remains a major cause of morbidity and mortality of children in the world, especially in developing countries, including Indonesia. Based on the results of the morbidity and mortality survey conducted Sub gastroenteritis in 2010, the death rate from gastroenteritis Cause Specific Death Rate by 23 about 100 thousand inhabitants and in infants Age Specific Death Rate by 75 about 100 thousand babies. While in the hospital Puri Husada Tembilahan, the overall proportion of infant gastroenteritis cases by 42.01% and the Case Fatality Rate by 3.12%. Has done research that aims to identify the characteristics of infants hospitalized patients with gastroenteritis in hospitals Puri Husada Tembilahan years 2011-2012, a descriptive case series design, using secondary data. The population is all infants hospitalized patients with gastroenteritis in 2011-2012 as many as 229 people, and a sample of 146 people were taken by simple random sampling. From the research found most babies with gastroenteritis at the age of < 6 months (87,7%), males (56,8%), self-employed parents work (69,2%), good nutrition status (64,4%), the main complaint vomiting (89,0%), the degree of mild dehydration (64,4%), complications (14,4%),management of intravenous fluid administrations/infusion (51,4%), the average treatment time 3,43 during the day and go home in a state of recovery (70,5%). Statistical test results obtained no significant difference in the proportion of state while returning by complications (X2 = 5,882 ; p = 0,053). There is no significant difference in the average long care by age (F = 2,678 ; p = 0,104), there was no significant difference in the average treatment time is based on the degree of dehydrations (F = 2,555 ; p = 0,081). To the hospital is recomended to improve the quality of service and complete the notes on the state of the card baby height measurement, the level of mother’s education and employment.Keywords: gastroenteritis, infant characteristics